RRI DENPASAR CULTURAL TALK MEDIA CULTURAL KNOWLEDGE EDUCATION MEDIA FOR THE YOUNG HINDU GENERATION OF BALI - Ni Putu Widhyawaty , (JKKB: Jurnal Kajian Komunikasi Budaya (JCCS: Journal of Cultural Communication Studies), 2024)
This research examines the two-way communication patterns implemented in the interactive dialogue program "Cultural Talk Show" based on Hinduism at Program 1 RRI Denpasar. Using cultural norms theory, this research examines how mass media, especially radio, can create an impression on audiences. This program is an innovation that combines telephone and internet technology to increase interactivity and listener reach. The research method used is qualitative with data collection through interviews, observation and literature study. The research results show that the two-way communication pattern implemented through an interactive dialogue format is successful in attracting active participation from listeners, especially the younger generation, and supports the preservation of Hindu culture and religion. This program also shows effectiveness in educational, socio-cultural and cultural preservation functions, even though it faces several challenges such as limited sources and determining broadcast topics. The implementation of advanced technology and appropriate communication strategies is key in maintaining the relevance and attractiveness of this program in the digital era.